Ion kinetics and ion sound generation under the development of modulation instability of an intense Langmuir wave in a plasma - Kirichok, A.V.; Kuklin, V.M.; Pryimak, A.V.; Zagorodny, A.G. (Вопросы атомной науки и техники, 2015)
The development of one-dimensional parametric instabilities of intense long-wave plasma waves is considered in terms of the so-called hybrid models, when electrons are treated as a fluid and ions are regarded as particles. The analysis is performed for both cases when the average plasma field energy is lower (Zakharov's hybrid model − ZHM) or greater (Silin's hybrid model − SHM) than the plasma thermal energy. Reduced absorption of the high-frequency (HF) field leads to the retardation of the HF field burnout within plasma density cavities and to the broadening of the HF spectrum. At the same time, the ion velocity distribution tends to the normal distribution in both ZHM and SHM. Аналізується розвиток 1D-параметричних нестійкостей інтенсивних довгохвильових ленгмюрівських хвиль у термінах так званих гібридних моделей, коли електрони описуються як рідина, а іони описуються частинками. Розглядаються випадки, коли середня енергія поля менше (гібридна модель Захарова) і більше (гібридна модель Силіна) теплової енергії плазми. Зменшення поглинання високочастотного поля відповідає уповільненню вигорання ВЧ-поля в утворених кавернах щільності плазми і уширенню спектра ВЧ-мод. При цьому функція розподілу іонів за швидкостями в моделях Захарова та Силіна за формою наближається до нормального розподілу. Анализируется развитие 1D-параметрических неустойчивостей интенсивных длинноволновых ленгмюровских волн в рамках так называемых гибридных моделей, когда электроны описываются как жидкость, а ионы описываются частицами. Рассматриваются случаи, когда средняя плотность энергии поля меньше (гибридная модель Захарова) и больше (гибридная модель Силина) плотности тепловой энергии плазмы. Уменьшение уровня поглощения высокочастотного поля соответствует замедлению выгорания ВЧ-поля в образовавшихся кавернах плотности плазмы и уширению спектра ВЧ-мод. При этом функция распределения ионов по скоростям в моделях Захарова и Силина по форме приближается к нормальному распределению.